2023
DOI: 10.1177/17562848231195680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of colon capsule endoscopy: a moving target?

Gohar Jalayeri Nia,
Ramesh P. Arasaradnam,
Anastasios Koulaouzidis

Abstract: The purpose of this article is to provide an overview of white light colon capsule endoscopy’s current clinical application, concentrating on its most recent developments. Second-generation colon capsule endoscopy (CCE2) is approved by the FDA for use as an adjunctive test in patients with incomplete colonoscopy and within Europe in patients at average risk, those with incomplete colonoscopies or those unwilling to undergo conventional colonoscopies. Since the publication of European Society of GI Endoscopy gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The stages of integrating artificial intelligence (AI) into the CCE process detailed by Robertson et al propose a scenario where AI could initially replace the pre-reading process and eventually take on the responsibility for analysing the entire CCE video prior to the clinician’s validation and reporting. 12 14 This proposal comprises of different stages. It suggested that the clinician would be presented with all the polyps’ images without a comprehensive review of the whole CCE video.…”
Section: Introductionmentioning
confidence: 99%
“…The stages of integrating artificial intelligence (AI) into the CCE process detailed by Robertson et al propose a scenario where AI could initially replace the pre-reading process and eventually take on the responsibility for analysing the entire CCE video prior to the clinician’s validation and reporting. 12 14 This proposal comprises of different stages. It suggested that the clinician would be presented with all the polyps’ images without a comprehensive review of the whole CCE video.…”
Section: Introductionmentioning
confidence: 99%